Promosi Wisata Desa Medowo Kabupaten Kediri Sebagai Desa Wisata - Pratiwi, Seli Septiana; Apriadi, Deny Wahyu; Kodir, Abdul; Shofa, Abd. Mu’id Aris (Universitas Ekuitas Indonesia, 2023)
The promotion strategy is the main factor for increasing the popularity of a region, including for the benefit of tourism. Regions in East Java were encouraged to develop the tourism sector causing an increase in tourist villages, one of which was carried out in Medowo village. The change in the focus of the village to become a tourist village is an opportunity for the local community to develop agricultural products into products that have a higher selling value. Product promotion needs to be shown carefully to keep up with the times. Changes in promotion through information technology require the public to be careful in choosing the right media and uploading interesting content. The purpose of this community service is to help the people of Medowo village develop the tourism sector and UMKM so that it has an impact on improving the economy and people’s welfare. Participation Rural Appraisal (PRA) is used as a method of community sevice by emphasizing solidarity among communities. The result is that the majority of people have a livelihood as farmers. There are three things that need to be considered by Medowo village to improve the tourism sector, namely (1) the uniqueness of the Medowo village area, (2) the target market for the tourism sector, and (3) the selection of social media and content that supports the tourism sector. The cillage community must be able to recognize the uniqueness of Medowo village, this can also be used as an opportunity to form new livelihoods in the UMKM sector. Keyword: Promotion strategy, tourist village, tourism. Abstrak Strategi promosi menjadi faktor utama untuk meningkatkan popularitas sebuah wilayah termasuk untuk kepentingan pariwisata. Wilayah di Jawa Timur didorong untuk mengembangkan sektor wisata menyebabkan peningkatan desa wisata, salah satunya dilakukan di Desa Medowo. Perubahan fokus desa menjadi desa wisata menjadi peluang bagi masyarakat setempat untuk mengembangkan produk hasil bumi menjadi produk yang memiliki nilai jual lebih tinggi. Promosi produk perlu diperlihatkan dengan cermat mengikuti perkembangan zaman. Perubahan promosi melalui teknologi informasi membutuhkan kecermatan masyarakat memilih media yang tepat dan mengunggah konten yang menarik. Tujuan pengabdian masyarakat ini untuk menunjukkan peluang dan potensi desa untuk berkembang menjadi desa wisata. Participation Rural Appraisal (PRA) digunakan sebagai metode pengabdian masyarakat dengan menekankan solidaritas diantara masyarakat. Hasilnya mayoritas masyarakat memiliki mata pencaharian sebagai petani. Terdapat tiga hal yang perlu diperhatikan oleh Desa Medowo untuk meningkatkan sektor wisata yaitu (1) keunikan wilayah Desa Medowo, (2) target pasar untuk sektor pariwisata, dan (3) pemilihan media sosial dan konten yang mendukung sektor pariwisata. Masyarakat desa harus mampu mengenali keunikan yang dimiliki Desa Medowo, hal ini juga bisa dijadikan peluang membentuk mata pencaharian baru pada sektor UMKM. Kata kunci: Strategi promosi, desa wisata, pariwisata.